Football in the land of the Soviets - Viñas, Carles, 1972-; Padilla, Toni, 1977-; Stobart, Luke (London : Pluto Press, 2022)
"Mistrusted and derided, instrumentalised and adored - the story of football in Tsarist and early Soviet Russia is as wild and intriguing as that of the country itself. In many ways it is the same story… Football in the Land of the Soviets offers a fresh perspective on a momentous chapter in modern political history. Carles Viñas shows how the Russian game was transformed in just a few decades: from a minor émigré pastime, to a modernising driver of society, to a vanguard for Soviet diplomacy and internationalism, and finally, with the first championship of the Soviet League in 1936, into a truly mass phenomenon. So exactly how did a bourgeois game end up as the collective passion of the Soviet working class? And why does it matter? Football in the Land of the Soviets brings these questions to the fore in this thrilling, unorthodox account of the fall of an imperial dynasty and the rise of the world's first socialist state."--publisher.
Football comes to tsarist Russia -- The British connection -- St. Petersburg - Russian football capital -- Industrialism, workers, and the rise of Muscovite football -- Morozovtsy - the first great team -- The newly created Russian Football Union and the Stockholm games -- The first National League championship -- "Wild football" - clandestinity, sport, and activism -- The impact of the 1914 Great War -- Tumultuous times and the 1917 revolution -- "White" football - conspiracy and espionage -- Civil war and sport's militarisation -- The third-international team -- Hygienists, proletkultists, and the concretisation of a sports model -- Isolation and diplomacy, a team at the country's service -- A mass sport in the USSR.
Translated from the Catalan.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 17, 2022).
JSTOR
Keywords: Soccer -- Russia -- History; Soccer -- Soviet Union -- History; Russia -- History -- Nicholas II, 1894-1917.; Soviet Union -- History -- 1917-1936.; Russie -- Histoire -- 1894-1917 (Nicolas II); URSS -- Histoire -- 1917-1936.; Soccer; HISTORY; Russia & the Former Soviet Union; Europe; 20th Century; Modern; Communism; Political Ideologies; POLITICAL SCIENCE; SPORTS & RECREATION; Sociology of Sports; Soccer; Russia; Soviet Union; 1894-1936; Electronic books; History